Quercus ilex recruitment in a drier world: A multi-stage demographic approach - Pérez-Ramos, Ignacio M; Rodriguez-Calcerrada, Jesus; Ourcival, Jean M; Rambal, Serge (Perspectives in Plant Ecology, Evolution and Systematics, 2013)
There is a growing interest in understanding and forecasting the responses of plant communities to projected changes of environmental conditions. Multi-stage demographic approaches, where plant recruitment is explored across multiple and consecutive stages, are essential to obtain a whole overview of the consequences of increasing aridity on tree recruitment and forest dynamics, but they are still rarely used. In this study, we present the results of an experimental rainfall exclusion aimed to evaluate the impact of projected increasing drought on multiple stage-specific probabilities of recruitment in a key tree species typical of late-successional Mediterranean woodlands (Quercus ilex L.). We calibrated linear and nonlinear likelihood models for the different demographic processes and calculated overall probabilities of recruitment along a wide range of microhabitat conditions. Rainfall exclusion altered Q. ilex recruitment throughout ontogeny. Seed maturation, seedling emergence and survival and, to a lesser extent, post-dispersal seed survival were the most sensitive demographic processes to decreased rainfall. Interestingly, both the identity of the most critical stages for recruitment and their specific sensitivity to rainfall manipulation depended largely on the yearly pattern of precipitation. The microhabitat heterogeneity strongly determined the success of recruitment in the study species. The experimental increase in drought displaced the peak of maximum overall recruitment towards the low end of the light gradient, suggesting that the dependence on shrubs for an effective recruitment in Q. ilex could be intensified under future environmental scenarios. In terms of phenotypic plasticity, Q. ilex seedlings responded more strongly to light availability than to experimentally increased drought, which could reduce its ability to persist under on-going environmental conditions due to climate change. Results from this study provide a full picture of the ecological and functional consequences of the projected rainfall reduction on tree recruitment and forest dynamics in two years of contrasting precipitation.
Keywords: climate change; functional traits; Mediterranean woodland; Microhabitats; regeneration niche; seedling growth

Quercus ilex recruitment in a drier world: A multi-stage demographic approach - Pérez-Ramos, Ignacio M.; Rodriguez-Calcerrada, Jesus; Ourcival, Jean M.; Rambal, Serge (Perspectives in Plant Ecology, Evolution and Systematics, 2013)
There is a growing interest in understanding and forecasting the responses of plant communities to projected changes of environmental conditions. Multi-stage demographic approaches, where plant recruitment is explored across multiple and consecutive stages, are essential to obtain a whole overview of the consequences of increasing aridity on tree recruitment and forest dynamics, but they are still rarely used. In this study, we present the results of an experimental rainfall exclusion aimed to evaluate the impact of projected increasing drought on multiple stage-specific probabilities of recruitment in a key tree species typical of late-successional Mediterranean woodlands (Quercus ilex L.). We calibrated linear and nonlinear likelihood models for the different demographic processes and calculated overall probabilities of recruitment along a wide range of microhabitat conditions. Rainfall exclusion altered Q. ilex recruitment throughout ontogeny. Seed maturation, seedling emergence and survival and, to a lesser extent, post-dispersal seed survival were the most sensitive demographic processes to decreased rainfall. Interestingly, both the identity of the most critical stages for recruitment and their specific sensitivity to rainfall manipulation depended largely on the yearly pattern of precipitation. The microhabitat heterogeneity strongly determined the success of recruitment in the study species. The experimental increase in drought displaced the peak of maximum overall recruitment towards the low end of the light gradient, suggesting that the dependence on shrubs for an effective recruitment in Q. ilex could be intensified under future environmental scenarios. In terms of phenotypic plasticity, Q. ilex seedlings responded more strongly to light availability than to experimentally increased drought, which could reduce its ability to persist under on-going environmental conditions due to climate change. Results from this study provide a full picture of the ecological and functional consequences of the projected rainfall reduction on tree recruitment and forest dynamics in two years of contrasting precipitation.
The following values have no corresponding Zotero field: publisher: Elsevier GmbH.
Keywords: climate change; functional traits; Mediterranean woodland; Microhabitats; regeneration niche; seedling growth

SEARCH FOR FACTORS MAINTAINING TERRICOLOUS BRYOFLORA RICHNESS IN ISOLATED HABITATS - THE CASE OF SCLEROPHYLLOUS OAK GROVES OF THE OCCIDENTAL BORDER OF THE MAURES MASSIF (VAR, FRANCE) - Hebrard, J P; Loisel, R (CRYPTOGAMIE BRYOLOGIE LICHENOLOGIE, 1994)
Processing (FAC) of 25 bryophytoecological releves and quantitative analysis of bryofloristical inventories from 4 forest structures (surface values respectively 3976, 6160, 13115 and 77617 m2) isolated within the vineyard near Pierrefeu-du-Var (siliceous substratum) show that, for what concerns sclerophyllous oaks ecosystems (Quercus ilex, more rarely Quercus suber), the more humid the local microclimate is, the greatest are richness and diversity of terricolous communities of bryophytes. The optimal conditions for preservation of richness in forest bryophytes are here realized at the Defens du Becasson (surface: 77617 m2, maximum width: 151 m), a north-facing side which is well protected against the drying action of dominant winds and where the architecture of the ligneous formations is heterogeneous. On the other hand, the diversity of available microhabitants in the 2 largest isolates (strong slope, presence of clearings and disturbed skirts) contributes to increase their global richness in bryophytes. Furthermore, the presence of a dense layer of shrubs limits the accumulation of dead leaves on soil surface, allowing a good spread of the bryophyte layer and correlatively an enrichment in forest taxa when ambient humidity is high enough.
APS
Keywords: bryophytes; Microhabitats; Quercus ilex; Quercus suber